The Sexual Lives of Men and Women with Disabilities: Attitudes From Male and Female Members of the General Public Toward Subjects with the Same Gender. - Berlingo-Tapp, Lauren; Dukes, Charles; Darling, Sharon M.; Finnegan, Lisa A. (Sexuality & Disability, 2026)
This study investigated public attitudes toward the sexual lives of individuals with disabilities. History demonstrates that people with disabilities have often been denied fundamental human rights, including sexual autonomy. Beyond societal barriers, even those closest to individuals with disabilities sometimes restrict or discourage sexual experiences due to fear, misunderstanding, or stigma. The present study examined how males and females from the general public view the sexual experiences of people with disabilities across three categories: physical, intellectual, and general (non-specified) disability. Participants (n = 993) completed a survey comprising a modified version of the attitudes toward sexuality–general public and attitudes toward sexuality–intellectual disability instruments, administered via Qualtrics. Data were collected using CloudResearch’s Prime Panels. Results indicated that female respondents reported more positive attitudes toward females, both with and without disabilities, engaging in a sexual life than did male respondents toward males with and without disabilities. Additionally, respondents expressed the least positive attitudes toward adults with intellectual disabilities having a sexual life. Study limitations and recommendations for future research are discussed.